Ecofeminism and Gilman’s Herland: a Gaardian approach - Abbasi, Pyeaam; Moslehi, Mahboubeh (Penerbit Universiti Kebangsaan Malaysia, 2016)
Charlotte Perkins Gilman (1860-1935) is an eminent American philosopher, lecturer, social critic, and known for her feminist utopian novel, Herland (1998). The novel is analysed based on Greta Gaard’s theory of ecofeminism that cites patriarchal religion, Darwin’s human evolutionary development, and the metaphorical or ideological explanations as the sources of the separation of culture from nature that lead to the self/other dualism. This study is an attempt to reject the self/other, man/woman and culture/nature dualisms of patriarchal thought, and show how women and nature are liberated from oppression. Gaard has shown that the claim for the superiority, separation, and domination of the self is based on the difference between self and other, where all things associated with self are privileged, and all things described as other are devalued. Gaard uses this self/other dualism to explain the patriarchal domination pertaining the supposed relationship between women and nature, since both are configured as ‘other’ and are separated from self associated with men and culture. She explains that patriarchal thought emphasises the differentiation of ‘self’ from ‘other’ and the connection of women and nature to justify the domination of both women and nature. This study will explore how Gilman declines the root cause of dualisms of culture/nature and man/woman as lying in the social construction of patriarchal religion and Darwin’s human evolutionary development through depicting a utopian maternal world. She undermines the paternal attitudes that are based on competition to possess and dominate both women and nature, and she makes the connections among men, women, and nature through education of the children in open fields to create the interconnections between nature and culture and denounce the oppression of these categories.